MODEL CHALLENGE BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF MAHASISWA - Naim, Suratman S.; Ibnu, Suhadi; Santoso, Aman (Graduate School of Universitas Negeri Malang, 2020)
Abstract: The purpose of this research was to determine the influence of challenge based learning model on students creative thinking ability. This research is used a quasy-experimental design of the type nonequivalent pretest-posttest control group design. The sample of this research consisted of students of Chemistry Education, Khairun University in the sixth semester, enrolling in the subject of Environmental Chemistry during education year in 2018/2019 from two classes. The experimental class was taught with challenge based learning model and the control class was taught with problem based learning model. The instrument of the research was a creative thinking ability tests with the type of open essay questions that had validity of 77.08% and Alpha Cronbach reliability coefficient of 0.896. The results showed that there was no statistically significant difference in creative thinking ability between the students from the two research classes (? = 0.05), although descriptively the creative thinking ability of the experimental class was better than the control class.Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh model challenge based learning terhadap kemamampuan berpikir kreatif mahasiswa. Penelitian ini menggunakan rancangan penelitian eksperimental semu tipe nonequivalent pretest-posttest control group design. Sampel penelitian ini terdiri dari mahasiswa Pendidikan Kimia, Universitas Khairun angkatan 2016 yang menempuh matakuliah Kimia Lingkungan pada tahun ajaran 2018/2019 dari dua kelas. Kelas ekperimen dibelajarkan dengan model pembelajaran challenge based learning dan kelas kontrol dibelajarkan dengan model pembelajaran problem based learning. Intrumen penelitian adalah tes kemampuan berpikir kreatif dengan jenis soal essay terbuka yang memiliki validitas isi 77,08% dan koefisien reliabilitas Alpha Cronbach 0,893. Hasil penelitian memperlihatkan bahwa tidak ada perbedaan yang signifikan antara kemampuan berpikir kreatif mahasiswa dari kedua kelas penelitian (? = 0.05), walaupun secara deskriptif kemampuan berpikir kreatif kelas eksperimen lebih bagus daripada kelas kontrol.